2017
DOI: 10.1007/s12015-017-9786-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual Contribution of Mesenchymal Stem Cells Employed for Tissue Engineering of Peripheral Nerves: Trophic Activity and Differentiation into Connective-Tissue Cells

Abstract: Adult peripheral nerves in vertebrates can regrow their axons and re-establish function after crush lesion. However, when there is extensive loss of a nerve segment, due to an accident or compressive damage caused by tumors, regeneration is strongly impaired. In order to overcome this problem, bioengineering strategies have been employed, using biomaterials formed by key cell types combined with biodegradable polymers. Many of these strategies are successful, and regenerated nerve tissue can be observed 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…On the other hand, the effect is related to the possible differentiation of MSCs into Schwann cells under the influence of trophic factors released from the proximal end of the cut nerve. However, this assumption does not always find experimental confirmation (Shen et al, 2010;Evaristo-Mendonca et al, 2018). In this study, we were also unable to show the possibility of differentiating MSCs into Schwann cells.…”
Section: Cell Biology Regenerative Medicinecontrasting
confidence: 64%
See 2 more Smart Citations
“…On the other hand, the effect is related to the possible differentiation of MSCs into Schwann cells under the influence of trophic factors released from the proximal end of the cut nerve. However, this assumption does not always find experimental confirmation (Shen et al, 2010;Evaristo-Mendonca et al, 2018). In this study, we were also unable to show the possibility of differentiating MSCs into Schwann cells.…”
Section: Cell Biology Regenerative Medicinecontrasting
confidence: 64%
“…There is evidence of vascularization improvement in the damaged nerve due to the use of cellular therapy (Tamaki et al, 2014; Petrova, Isaeva, Kolos, and Korzhevskii, 2018; Evaristo-Mendonca et al, 2018). In our previous work, we showed that the number of microvessels in the damaged rat nerve trunk increases one and a half times after the application of MSCs (Petrova, 2018;Evaristo-Mendonca et al, 2018). Our current explanation of this fact is that MSCs produce angiogenic factors.…”
Section: Cell Biology Regenerative Medicinementioning
confidence: 86%
See 1 more Smart Citation
“…Instead, investigators have focused on the regenerative potential of adult stem cell lineages. Mesenchymal stem cells are an easily expandable, multipotent cell population that may differentiate into Schwann cell‐like cells and are capable of releasing a range of neurotrophins, growth factors, and interleukins . There are many sources, including bone marrow stromal cells (BMSC), from which mesenchymal stem cells can be harvested .…”
mentioning
confidence: 99%
“…Mesenchymal stem cells are an easily expandable, multipotent cell population that may differentiate into Schwann cell-like cells and are capable of releasing a range of neurotrophins, growth factors, and interleukins. 3 There are many sources, including bone marrow stromal cells (BMSC), from which mesenchymal stem cells can be harvested. [4][5][6][7] However, the practical difficulty of harvesting BMSCs, including donor site pain and morbidity, limits the feasibility of using it in clinical practice.…”
mentioning
confidence: 99%